2008
DOI: 10.1002/bit.22173
|View full text |Cite
|
Sign up to set email alerts
|

Five year maintenance of the inducible expression of anthranilate synthase in Catharanthus roseus hairy roots

Abstract: Transgenic hairy root cultures have the potential to be an industrial production platform for a variety of chemicals. This report demonstrates the long-term stability of a transgenic Catharanthus roseus hairy root line containing the inducible expression of a feedback-insensitive anthranilate synthase (AS). After 5 years in liquid culture, the presence of the inserted AS gene was confirmed by genomic PCR. The inducible expression of AS was confirmed by enzyme assay and by changes in terpenoid indole alkaloid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…1b), was confirmed by PCR in both the Bv 42 and Bv18HR clones following five years of cultivation which confirmed stability of root clones. This corroborates earlier finding the long term stability of the concerning anthranilate synthase gene expression in Catharanthus roseus hairy roots (Peebles et al, 2008). Growth kinetic analysis revealed that both the HR clones attained their maximum growth potentials on the 45 days of culture in full strength MS media.…”
Section: Growth Kinetics Vanillin Production and Real Time Expressiosupporting
confidence: 89%
See 2 more Smart Citations
“…1b), was confirmed by PCR in both the Bv 42 and Bv18HR clones following five years of cultivation which confirmed stability of root clones. This corroborates earlier finding the long term stability of the concerning anthranilate synthase gene expression in Catharanthus roseus hairy roots (Peebles et al, 2008). Growth kinetic analysis revealed that both the HR clones attained their maximum growth potentials on the 45 days of culture in full strength MS media.…”
Section: Growth Kinetics Vanillin Production and Real Time Expressiosupporting
confidence: 89%
“…It is pertinent to mention that the stable expression of the HCHL transgenes along with the vanillin synthesizing potential of both the HR clones of Bv after five year of their establishment (Rahman et al, 2009) emphasized the significance of the present study, in view of the fact that long term expression of transgenes remained, by and large unpredictable as found in cases of Cinchona ledgeriana and Catharanathus roseus hairy roots (Peebles et al, 2008). Undoubtedly the presently observed stabilization of the transgene after prolong culture period comply with the essentials prerequisite for the proper functioning and utilization of the targeted gene activity in terms of vanillin synthesis.…”
Section: Effect Of Precursor Feedingmentioning
confidence: 92%
See 1 more Smart Citation
“…Datura stramonium hairy roots showed stable alkaloid production for 5 years . C. roseus hairy roots have been reported to maintain the stability of an inducible GFP gene for 4.5 years and an inducible anthranilate synthase (AS) gene for 5 years . This article further demonstrates that C. roseus hairy root lines can maintain inducible expression of a gene for 11 years.…”
Section: Introductionmentioning
confidence: 76%
“…The cultures were then frozen at −80°C until they were lyophilized. Tryptophan (Sigma Aldrich), tryptamine (Sigma Aldrich), ajmalicine (AvaChem Scientific), serpentine (AvaChem Scientific), catharanthine (Qventas), hörhammericine (gift from Dr. Jacqueline V. Shanks at Iowa State University), lochnericine (gift from Dr. Jacqueline V. Shanks at Iowa State University) and tabersonine (AvaChem Scientific) were extracted and quantified by a previously reported HPLC based protocol …”
Section: Methodsmentioning
confidence: 99%